Contribution to the Cuban flora catalogue: endemics in the ophiolites derivate soils - López Almirall, Antonio (Botanica Complutensis, 2013)
The Cuban regions with predominance of ophiolites are known to have more endemics plants than bordering regions. The combined wealthof those floras is such that to understand the patterns of distribution of the Cuban flora is necessary to know those patterns in ofilitic regions. Goodindicators of the total wealth are the endemic components. With that objective here is published a cartographic diagram of Cuban regions whereit prevail the mentioned rocks, and a list of Cuban endemic taxa collected there. In the identified territories has been recognized 1603 infra genericendemic taxa of 106 families and 420 genus. Of those total, 741 are exclusive of ophiolitic regions. In the soils derivate from ophioliticsrocks mainly taxa from the North Andean evolutionary group are predominate.